Do past climate states influence diversity dynamics and the present‐day latitudinal diversity gradient?. Issue 5 (6th March 2014) - Huang, Shan; Roy, Kaustuv; Jablonski, David
Abstract Aim To identify the role of climate variations over geological time in shaping present‐day diversity patterns, particularly the latitudinal diversity gradient (LDG; the decrease of taxonomic diversity from low towards high latitudes), using marine bivalves as a model system. Location World‐wide. Methods We use the fossil record of extant and extinct bivalve taxa and information on global palaeoclimate states to evaluate how the climate state at the beginning of the evolutionary history of individual families influenced (a) their diversification dynamics through subsequent climate changes and (b) their present‐day LDG. For (a), we estimated per‐family genus origination and extinction rates during the last cool interval in the late Cenozoic and overall genus origination and extinction rates since the early Palaeozoic. For (b), we compared LDG slopes and oldest fossil occurrences of extant families with palaeoclimate data. We also tested whether such dynamics vary with life habits. Results Families that originated in warm intervals tend to have higher extinction rates in the (cool) late Cenozoic and occasionally in other cool intervals. However, in contrast to the results of Romdal et al. (Global Ecology and Biogeography, 2013, 22, 344–350), present‐day LDG slopes do not vary with the climate state at the time of family origination, regardless of the palaeoclimatic scheme used. Infaunal living families have marginally higher origination rates in the late Cenozoic, but their LDG slopes do not differ significantly from the epifaunal families. In contrast, feeding habit appears to affect family LDG slopes, but not late Cenozoic diversification rates. Main conclusion For marine bivalves, ancestral climate state appears to influence subsequent diversification dynamics with clades originating in warm intervals showing higher extinction rates during intervals of global cooling, but ancestral climate has no detectable influence on present‐day LDGs.